Hybrid polymeric composites based on polyethylene and lignin. (13th August 2009) - Samal, S.K.; Fernandes, E.G.; Corti, A.; Chiellini, E.
The bio-macromolecules are emerging as an important component for minimising energy consumption, waste generation and economic development. In consumer product segments including packaging, health care products, agricultural mulch films and disposable items, these materials have a great request. Polyethylene-lignin low cost bio-based hybrid materials were formulated following a statistical mixture design. Composites were compatibilised with ethylene vinyl alcohol copolymer and characterised by TGA, DSC, SEM and mechanical properties.